Judicial control over legislative body - Mokhtar, Khairil Azmin (2016)
Parliament is one of the three main organs of the government. Although Malaysia does not practice the Doctrine of Parliamentary Sovereignty (Supremacy) like the United Kingdom, Parliament is the most fundamental democratic institution in the country and forms an integral part of our constitutional arrangements. As one of the key state institutions in a democratic system of governance parliament has a critical role to play in promoting democracy and good governance. Comprised by the democratically elected representatives of the people, parliaments have the honorable task to ensure government by the people and for the people. In the performance of their key functions of legislation, representation and oversight, parliaments can actively engage in the development and implementation of laws, policies and practices that promote democracy and good governance. Like other jurisdictions, the Malaysian parliament can create or end any law, or can change any law made by earlier parliaments. Additionally, the Malaysian courts have power to declare primary legislations made both by the federal and state legislatures void based on articles 4(1), 74 and 75 of the Federal Constitution. However, this does not mean that the court is superior to parliament as the control that judiciary has over the parliament is restricted. The court’s limited role is to ensure that parliament does not transgress the boundaries set by the Federal Constitution, and to ensure the power exercised by parliament is valid and within its competence. Under the Doctrine of Separation of Powers, all State organs are independent of each other. Although every organ must check other organs to ensure the power is balanced, they cannot usurp the role and power of other organs. Thus the court under no circumstances is allowed, either directly or indirectly, to undermine the autonomy of the parliament or restrict its freedom. The court as the watchdog of the constitution has the duty to safeguard the constitution. The court’s power however does not extend to ‘controlling’ or influencing parliament. The parliament is the beacon of will of the people in a sovereign nation. It must be allowed to operate freely and independently; free from any interference by other organs of the government and by any element coming from beyond or within the country. To achieve this purpose, certain immunities and privileges have been granted to parliament and its members. Parliamentary privileges are an essential part of our parliamentary democracy. It ensures that Members of Parliament are able to speak freely in debates, and protects Parliament’s internal affairs from interference of the courts. The Federal Constitution guarantees independence of the legislatures as can be seen in articles 63 and 72. The court fully understands the sanctity of parliamentary privileges. The courts in Malaysia had consistently tried to avoid from reviewing the decision of the legislative body as it had recognized the inviolability of the latter’s proceedings. This is evident from a number of courts’ decisions. Parliament and its members are thus free to exercise their powers and discharge their duties without fear or favour.